Poor sleep quality may contribute to dysfunctional illness perception, physical and emotional distress in hospitalised patients: results of a national survey of the Italian Society of Consultation‐Liaison Psychiatry. (22nd April 2022) - Palagini, Laura; Zerbinati, Luigi; Balestrieri, Matteo; Belvederi Murri, Martino; Caruso, Rosangela; D'Agostino, Armando; Ferrara, Maria; Ferrari, Silvia; Minervino, Antonino; Massa, Lucia; Milia, Paolo; Miniati, Mario; et al.
Summary: Distress associated with physical illness is a well‐known risk factor for adverse illness course in general hospitals. Understanding the factors contributing to it should be a priority and among them dysfunctional illness perception and poor sleep quality may contribute to it. As poor sleep quality is recognised as a major risk factor for health problems, we aimed to study its association with illness perception and levels of distress during hospitalisation. This cross‐sectional study included a consecutive series of 409 individuals who were hospitalised in medical and surgical units of different hospitals located throughout the Italian national territory and required an assessment for psychopathological conditions. Sleep quality was assessed with the Pittsburgh (Sleep Quality Index), emotional and physical distress with the Edmonton Symptom Assessment System (ESAS), and illness perception with the Brief Illness Perception Questionnaire (BIPQ). Differences between groups, correlations and mediations analyses were computed. Patients with poor sleep quality were more frequently females, with psychiatric comorbidity, with higher scores in the ESAS and BIPQ. Poor sleep quality was related to dysfunctional illness perception, and to both emotional and physical distress. In particular, by affecting cognitive components of illness perception, poor sleep quality may, directly and indirectly, predict high levels of distress during hospitalisation. Poor sleep quality may affect >70% of hospitalised patients and may favour dysfunctional illness perception and emotional/physical distress . Assessing and treating sleep problems in hospitalised patients should be included in the routine of hospitalised patients.